Produksi Dan Kandungan Gizi Rumput Gajah (P. purpureum) Dan Rumput Raja (P. purpupoides) Yang Ditumpangsarikan Dengan Tanaman Jati - Nuraini Jamaran (Universitas Andalas, 2006)
This research was objected to study the effect of plant densities on the biomass production and nutrient contents of elephant and king grasses intercropped with teak plant. The teak trees were about 9 months old and planted with the space between trees of 3 x 3 m. Elephant and king grasses were planted between teak plant in 3 difference densities of: 1.5 m x 0.80 m (one line density), 1 m x 0.80 m (two lines density), and 0.75 x 0.80 (three lines density). Parameters observed included: plant high, amount of buds/bunch, fresh and DM production, high and diameter of teak trees. Data were statistically analyzed for variance analysis in split plot design. Two kinds of grasses as main plot and 3 plant densities as sub plot with 3 replications. The results showed plant densities gave not significant effect on protein and crude fiber content of grasses, but crop production in both fresh and DM form increased significantly by increasing plant densities. Moreover, the development of teak trees was also significantly affected by grasses. Teak trees intercropped with king grass showed higher tree that intercropped with elephant grass.